Модифікація методу параметризації цільової функції для розв’язання задачі умовної мінімізації - Голубощенко, Р. В. (ХНУРЕ, 2023)
This work is written in order to show a reader one quite easy but helpful mathematical improvement of objective function parametrization method. The biggest attention is paid to proof of modified method viability. Also, the geometrical representation is given.
Keywords: метод параметризації цільової функції; максимізація функції; обмеження-нерівності; квадратична функція штрафу